GAMBARAN SIKAP KERJA DAN KELUHAN NYERI PUNGGUNG BAWAH PADA PEKERJA PENENUN SONGKET PANDAI SIKEK DI JORONG KOTO TINGGI NAGARI PANDAI SIKEK KABUPATEN TANAH DATAR SUMATRA BARAT - Friska Eka Fitria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Rheumatoid arthritis is a disease with the second sequence number out of 10 most diseases in Puskemas Koto Baru, Kabupaten Tanah Datar, Provinsi Sumatera Barat. this disease is a joint pain disease. within 1 month, there were 49 people who complained of joint pain and 10 of them had low back pain. the purpose of this study is to describe the work posture and complaints of low back pain in the songket weaver worker pandai sikek in Jorong Koto Tinggi Nagari Pandai Sikek Kabupaten Tanah Datar Provinsi Sumatera Barat. this type of research is quantitative descriptive with research instruments using REBA and Nordic Body Map questionnaire. the number of samples in this study were 26 people. this research was conducted in Jorong Koto Tinggi Nagari Pandai Sikek Kabupaten Tanah Datar Provinsi Sumatera Barat with the research time from november 2019 to october 2020. data analysis used univariate analysis. the results showed that most of the respondents were in the medium risk level category, which means that they needed action to improve their work posture with a percentage of 61.5% (16 people). almost all weavers reported experiencing frequent complaints of low back pain with a percentage of 84.6% (22 people). weavers are advised to warm up before work and stretch the muscles more often while working.